Molecular phylogeny of Saudi Arabian Tetraena Maxim. and Zygophyllum L. (Zygophyllaceae) based on plastid DNA sequences (Bangladesh Journal of Plant Taxonomy, 2017)
In order to provide a basis for better understanding of phylogenetic relationships of Saudi Arabian Tetraena Maxim. and Zygophyllum L., 44 specimens representing seven taxa, were reconstructed based on chloroplast DNA data of rbcL and trnL-F. The combined chloroplast (rbcL and trnL-F) contributed more phylogenetically informative characters than in individual regions. Phylogenetic analysis of the combined chloroplast (rbcL and trnL-F) and in individual regions based on both of Maximum Parsimony and Bayesian criteria showed that the Saudi Arabian species of Tetraena and Zygophyllum were monophyletic. Zygophyllum fabag L. was nested in one clade with Z. xanthoxylum (Bunge) Engl. (Asian species), and all taxa of Tetraena were distributed in other clades.Bangladesh J. Plant Taxon. 24(2): 155–164.